Strategi Meningkatkan Kualitas Perekonomian Lokal di Soka Wetan, Kabupaten Sleman, Yogyakarta - Agus Mulyono; Danang Sunyoto; Nur Hafifatul Janiyah; Hafiza Hulwa Yumna; Moh Noruddin; Zahron Bayu Rizky; Ivan Setiawan; Yohanes David Semunya; Joao Bosco De Jesus Santos Maring; Harnal Mayor; Korinus Melaluan Metalmety; Paulinus Raga Retong (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
Soka Wetan Village, Merdikorejo, Tempel, has great potential to improve the quality of the local economy. This potential can be explored through various natural and human resources available in the village. However, currently the village is still lagging behind in terms of development and economic development. This journal aims to examine appropriate strategies for building and developing the potential of the people of Soka Weta Village, Merdikorejo, Tempel, with the aim of improving the quality of the local economy.